Long-Run Money Demand Function: Search for Stability in Twenty (20) Non-EMU Member Countries - Asiedu, Michael; Bimpong, Patrick; Khela, Thomas Hezkeal Nan; Arthur, Benedict (Asian Journal of Economic Modelling, 2021)
This study examined the long-run money demand function in search for stability in twenty (20) Non-EMU member countries by applying Co-integration, an ARDL bounds test, CUSUM, and CUSUM squared estimation techniques to data spanning 1996 – 2019. We found co-integrating relationship between money demand and its determinants for all the countries under consideration (19 out of 20) except for Sweden. Stability in the money demand was also confirmed in seven (7) countries (Russia, Hungary, Montenegro, Bosnia, Bulgaria, Romania, and Croatia) based on both the CUSUM test results and CUSUM squared test. The remaining countries exhibited partial stability as indicated by the non-simultaneous stability of the CUSUM and CUSUM squared test. The divergence and heterogeneity found in the money demand functions and its determinants in these countries only give further impetus to their non - membership in the Eurozone. Hence there is the need for stability and convergence in the monetary policy management and money demand function to be admitted into the Eurozone holding other conditions fixed.